AKUNTANSI BERKELANJUTAN PADA UMKM: PEMAHAMAN ATAS LAPORAN KEBERLANJUTAN - Gautama, Bryan; Mahandito, Tasdik; Salsabila, Dwi (Jurnal Riset Akuntansi, 2023)
There is concern over intergenerational problems caused by the economic development carried out by countries in the world. As a form of this awareness, the global community compiled the Global Reporting Index (GRI) which is an international initiative that focuses on reporting and establishes at least the principles of risk management and continuous improvement. This study aims to determine the application of GRI indicators as a sustainability report by MSMEs in Indonesia. The implementation of GRI is important for MSMEs to encourage sustainability, considering that MSMEs are the largest group that contributes to the Indonesian economy. The research was conducted using content analysis, descriptive analysis, and confirmatory factor analysis (CFA) to determine the indicators that are most easily understood and applied by MSMEs so that they can be proposed as a sustainability report format. The results showed that there are 28 indicators that can be proposed as a sustainability report format. Meanwhile, 10 other indicators that are difficult for MSMEs to understand are not proposed as report formats.